The Development Of “Advance Os” Teaching Model On Mathematics For Primary School Students - Joko Sulianto, Sunardi, Sri Anitah & Gunarhadi (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
The aim of this development research study is for making a prototype of Advance OSteaching model on Maths for primary school students. It is based on Gall, Gall, & BorgResearch and Development method which is developed from Dick & Carey’s theory. Thesteps are now simplified into 3 steps: previous study, model development, and modelmeasurement. On the first step–previous study–, the reseachers applied descriptivequalitativeapproarch by doing library reasearch, field research of the product, and getting thepreliminary research finding. On the second step–model development–, teaching model wasdeveloped by appliying Dick & Carey’s model. This step was a compiling step of planning,developing draft of product, preliminary test, first revision, and widely test of product. Thelast step–model measurement–is the step for measuring the effect of the product. It was doneby conducting “true experimental design” using “posttest–only control design”. The researchfinding of this study is Advance OS teaching model on mathematics for primary schoolstudents. It has four big steps on appliying the model: presenting advance organizer,eksploring scientific approach, presenting organizer, and open-ended step includingempowering cognitive structure by giving open-ended questions to the students.Keywords: advance OS, research and development, primary school